Drowz guardian - Chen, Kai Jun; Meah, Chee Yong; Pang, Cheng Yao; Yong, Chee Yun (2024)
Statistics in Malaysia indicate that driver carelessness is a significant contributing factor to road accidents, often resulting from occurrences of microsleep. Over 20% of road accidents in the country are attributed to drivers falling asleep of feeling drowsy. The availability of microsleep prevention products in the Malaysian market is limited. The ADAS system is currently limited to expensive or high-spec cars, which creates an excellent opportunity for us to focus on a niche market segment and promote our product. Road Guard Technologies offers a microsleep preventor named “Drowz Guardian” by developing an eye detection technology to identify the presence or absence of driver drowsiness. This product aims to reduce accidents caused by microsleep, a common hazard among drivers. The driver will be alerted via alarm buzzer if they are in a drowsy state. Upon the driver's awakening, the alarm buzzer will stop sounding. Our product, Drowz Guardian, is unique and different from the other products in the market. The current microsleep prevention product available in Malaysia's market is a behind-the-ear wearable device, but it may cause discomfort for individuals who drive long distances or for drivers who wear glasses. As first movers, we employ eye detection technology to detect whether the driver is in a microsleep situation. Our customer segments are budget-conscious consumers, entry-level car buyers, and e-hailing or taxi drivers. They usually buy or use cars without ADAS and specifically lack a microsleep prevention feature. This product will be necessary for taxi or e-hailing drivers, as fatigue and extended hours of driving increase the risk to microsleep.